1978
DOI: 10.1073/pnas.75.4.1867
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent regulator protein: Localization in mitotic apparatus of eukaryotic cells

Abstract: Calcium-dependent regulator protein is a low molecular weight (17,000) (7) further demonstrated that the activation required micromolar levels of calcium. Hence, the protein is referred to as the Ca2+-dependent regulatory protein (CDR). Wang and coworkers (8, 9) first noted the structural similarity between CDR and troponin-C, the calcium-binding subunit of troponin that regulates skeletal muscle ATPase activity and muscle contraction. We have isolated CDR from rat testes and have shown that the primary amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(82 citation statements)
references
References 27 publications
4
78
0
Order By: Relevance
“…Furthermore, microinjection of calcium chelators inhibits mitosis (57-59), again implicating calcium in this process. Finally, indirect immunofluorescence has localized calmodulin to the kinetochore microtubules of the mitotic apparatus (60,61), and, in a related approach, fluorescently labeled calmodulin microinjected into cells binds to the kinetochore microtubules (62,63). Taken together, these studies strongly implicate calcium and calmodulin in the controlled depolymerization of microtubules that is necessary for anaphase A.…”
Section: Fig 7 Western Blot Analysis Of P62 Phosphorylated In Vivomentioning
confidence: 62%
“…Furthermore, microinjection of calcium chelators inhibits mitosis (57-59), again implicating calcium in this process. Finally, indirect immunofluorescence has localized calmodulin to the kinetochore microtubules of the mitotic apparatus (60,61), and, in a related approach, fluorescently labeled calmodulin microinjected into cells binds to the kinetochore microtubules (62,63). Taken together, these studies strongly implicate calcium and calmodulin in the controlled depolymerization of microtubules that is necessary for anaphase A.…”
Section: Fig 7 Western Blot Analysis Of P62 Phosphorylated In Vivomentioning
confidence: 62%
“…There is also a coincident localization of cold-stable microtubules and CaM to kinetochore-to-pole fibers of the mitotic apparatus (31). Preliminary evidence (unpublished observations) indicates the STOP145 antibody binds selectively to the cold-stable kinetochore-to-pole microtubules of cultured cells.…”
Section: Discussionmentioning
confidence: 91%
“…Those rats that received ACTH for a total of 16 (24,25) and Andersen et al (26) found calmodulin staining associated with a stress cable (actinlike) pattern in quiescent cells, but no nuclear staining was observed. Dividing cultured cells, however, had certain areas of the mitotic apparatus that were heavily stained for calmodulin.…”
Section: Resultsmentioning
confidence: 99%